Rehabilitation of the spine following sports injury - Sampsell, E. (Clinics in Sports Medicine, 2010)
The spine plays an essential role in the contribution toward athletic performance. As the central pillar of the body, the structures of the spine are susceptible to injury related with sports participation. This article identifies many of the most commonly seen sports-related injuries to the spine, and discusses practical rehabilitative interventions to manage such injuries. Anatomic considerations, biomechanical movements, and tissue properties are explained to better understand the clinical expectations associated with each of the injuries described.